(untitled) (Research, Society and Development, 2020)
This article presents the results of a research whose objective was to make possible the creation of a hacker culture in the classroom through proposals for the implementation of collaborative works, active methodologies and the discussion of collective evaluation approaches without leaving aside the individual one. The qualitative research was developed through a bibliographical revision regarding the hacker culture and also of the reflection about the current learning process. In this sense, some proposals of active methodologies and online support tools were presented, which provide a collaborative and innovative environment. Among the results discussed, we highlight the need for a remodeling of the approaches applied in the classroom, evaluation procedures and the teacher’s own role in the support and development of this hacker culture.